Analysis of The Compressive Strength of K 225 Concrete Using Palm Oil Shell Waste as A Particular Replacement of Coarse Aggregates High School Of Indragiri Rengat Technology - Wiranta, Pirman Jaka; Agustin, Sri; Trisnawati, Lisa (Kirana Publisher (KNPub), 2023)
Sand, coarse aggregate, and fine aggregate make up the building material known as concrete. Cement and water are used to bind these components together. The production of building construction is the typical application for using concrete (Atamini & Moestafa, 2018). In this study, researchers used a combination of 1%, 3%, and 5% shells from palms at ages 7, 14, and 21 days to measure the compressive strength of concrete using quality K-225. Concrete that is 21 days old or older because, according to PBI 1974, the strength of concrete is nearly 100% at this age. According to the results of the compressive strength test, the compressive strength of the 1% concrete mixture after 21 days was 238.40 kg/cm 2, the compressive strength of the 3% mixture after 21 days was 236.58 kg/cm 2, and the compressive strength of the 5% mixture after 21 days was 219.44 kg/cm 2. The inclusion of palm shells for quality K-225 can be employed at a mixture of 1% to 3% to obtain the required compressive strength, as can be observed from numerous modifications in the percentage of the combination. Keywords : compressive strength, aggregate, palm shell